An origami-inspired endoscopic capsule with tactile perception for early tissue anomaly detection - Ge,Y; Zong,R; Chen,X; Nanayakkara,T (IEEE Robotics and Automation Letters, 2024)
Video Capsule Endoscopy (VCE) is currently one of the most effective methods for detecting intestinal diseases. However, it is challenging to detect early-stage small nodules with this method because they lack obvious color or shape features. In this letter, we present a new origami capsule endoscope to detect early small intestinal nodules using tactile sensing. Four soft tactile sensors made out of piezoresistive material feed four channels of phase-shifted data that are processed using a particle filter. The particle filter uses an importance assignment template designed using experimental data from six known sizes of nodules. Moreover, the proposed capsule can use shape changes to move forward or backward under peristalsis passively. In the experiment, it was able to return to a specific area for repeated detection in a straight, two-dimensional intestinal model. Experimental results show that the proposed capsule can detect nodules of more than 3 mm diameter with 100% accuracy.